Analysis of Level of Student Learning Independence Through Phet Simulation Assisted Padlet Media Implementation - Az Zahro, Siti Fatimah; Supahar, Supahar; Wilujeng, Insih; Puspita Sari, Mega Indah; Handayani, Novia Amarta (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
Curriculum 2013 emphasizes education that can build an independent attitude in students. This study aimed to measure the level of student learning independence by implementing e-learning padlets assisted by PhET Simulation. The method used is descriptive quantitative where the sample involved is 35 people who are determined by cluster random sampling technique. The data collection technique used a learning independence questionnaire. Based on descriptive quantitative data analysis techniques, the results of research on the learning independence profile of students are based on five indicators, namely the responsible indicator of 76% in the high category, 63% initiative in the medium category, 65% confidence in the medium category, motivation 79% in the middle category. high category, and discipline of 86% in the very high category. The results of this study can be used as a basis for developing science learning media that is integrated with ICT to facilitate student learning independence.